Effect of Patient–Anesthesiologist Gender Concordance and Analgesic Modality on Postoperative Pain and Analgesic Requirements in Patients Undergoing Breast Surgery - Mustafa Kemal Şahin; Eda Cennet Caferoglu; Muhammed Burak Çalışıcı; Arif Timuroğlu (Ahi Evran Medical Journal, 2026)
Purpose: The potential impact of provider-related factors, including anesthesiologist sex, on postoperative pain and analgesic requirements remains an area of ongoing investigation. While gender dynamics have been explored in various clinical settings, their role in perioperative pain outcomes has not been fully elucidated, particularly in breast surgery patients.Materials and Methods: This prospective observational study included 127 female patients undergoing elective breast surgery under standardized general anesthesia. Patients were grouped according to anesthesiologist sex. Postoperative pain scores (VAS at 0, 6, 12, and 24 hours), total opioid consumption within 24 hours (morphine equivalents), rescue analgesia requirements, and early postoperative complications were recorded. Multivariable linear regression analysis was performed to identify independent predictors of opioid consumption, including anesthesiologist years of experience as a potential confounder.Results: Patients managed by female anesthesiologists had higher postoperative opioid consumption compared with those managed by male anesthesiologists (mean difference: 2.54 mg, 95% CI [1.29 to 3.80], p<0.001). Pain scores over the first 24 hours were also higher in the female-provider group (p=0.031), and the need for rescue analgesia was more frequent (36.2% vs. 21.7%, p=0.042). No significant difference was observed in early postoperative complications (p=0.084). In multivariable analysis, anesthesiologist sex remained an independent predictor of opioid consumption after adjustment for age, BMI, operative duration, ASA status, and anesthesiologist experience (p<0.001)Conclusion: Anesthesiologist sex was independently associated with postoperative opioid consumption and pain outcomes in patients undergoing breast surgery, independent of anesthesiologist experience and other measured confounders. These findings suggest that provider-related factors may influence perioperative pain management; however, causal inference remains limited, and the results should be interpreted within the context of multidisciplinary care pathways.